Cetuximab PET delineated changes in cellular distribution of EGFR upon dasatinib treatment in triple negative breast cancer - Brooke N. McKnight; Seongho Kim; Julie L. Boerner; Nerissa T. Viola (Breast Cancer Research, 2020)
Abstract Background At least 50% of triple negative breast cancer (TNBC) overexpress the epidermal growth factor receptor, EGFR, which paved the way for clinical trials investigating its blockade. Outcomes remained dismal stemming from mechanisms of resistance particularly the nuclear cycling of EGFR, which is enhanced by Src activation. Attenuation of Src reversed nuclear translocation, restoring EGFR to the cell surface. Herein, we hypothesize that changes in cellular distribution of EGFR upon Src inhibition with dasatinib can be annotated through the EGFR immunopositron emission tomography (immunoPET) radiotracer, [89Zr]Zr-cetuximab. Methods Nuclear and non-nuclear EGFR levels of dasatinib-treated vs. untreated MDA-MB-231 and MDA-MB-468 cells were analyzed via immunoblots. Both treated and untreated cells were exposed to [89Zr]Zr-cetuximab to assess binding at 4 °C and 37 °C. EGFR-positive MDA-MB-231, MDA-MB-468, and a patient-derived xenograft were treated with dasatinib or vehicle followed by cetuximab PET imaging to compare EGFR levels. After imaging, the treated mice were separated into two groups: one cohort continued with dasatinib with the addition of cetuximab while the other cohort received dasatinib alone. Correlations between the radiotracer uptake vs. changes in tumor growth and EGFR expression from immunoblots were analyzed. Results Treated cells displayed higher binding of [89Zr]Zr-cetuximab to the cell membrane at 4 °C and with greater internalized activity at 37 °C vs. untreated cells. In all tumor models, higher accumulation of the radiotracer in dasatinib-treated groups was observed compared to untreated tumors. Treated tumors displayed significantly decreased pSrc (Y416) with retained total Src levels compared to control. In MDA-MB-468 and PDX tumors, the analysis of cetuximab PET vs. changes in tumor volume showed an inverse relationship where high tracer uptake in the tumor demonstrated minimal tumor volume progression. Furthermore, combined cetuximab and dasatinib treatment showed better tumor regression compared to control and dasatinib-only-treated groups. No benefit was achieved in MDA-MB-231 xenografts with the addition of cetuximab, likely due to its KRAS-mutated status. Conclusions Cetuximab PET can monitor effects of dasatinib on EGFR cellular distribution and potentially inform treatment response in wild-type KRAS TNBC.